Comment: Is CAP addressed to support family farm? - Adele Coppola (Economía Agraria y Recursos Naturales)
The contribution of De Castro et al. in this issue (De Castro et al., 2014) underlines the role that small farms play in the EU agriculture and highlights how the recent CAP reform meets specificities and needs of this farming model. As the majority of EU farming are family farms and most of them are small either in physical or in economic terms, small-scale and family farming concepts are often used in an interchangeable way.